Amelanotic Malignant Melanoma Mimicking Hemangioma of the Hand: One Case Report and Literature Review - Lei MA; Xinghua GAO (Cancer Biology & Medicine, 2009)
Malignant melanoma (MM) is one of the most deadly cancers[1]. Althoughthe disease accounts for only about 4% of skin cancer relatedcases, it is responsible for about 79% of skin cancer deaths[2]. Earlydiagnosis of MM is, therefore, essential for appropriate treatmentdecision and, in turn, may give patients the best chance for prolongedsurvival[3-5]. About 6% to 8% of malignant melanomas lack typicalpigmentation and tend to be managed as benign lesions, making accurateearly diagnosis difficult[6]. Though subungual MM is rare,representing between 0.7% to 3.5% of all malignant melanomas inthe general population[7], delays in diagnosis and misdiagnosis resultin a poorer prognosis than MM at other sites[8]. We report a case ofamelanotic subungual melanoma with distant lymph nodes metastasiswhich mimicked hemangioma. The clinical features and differentialdiagnosis should alert both dermatologists and other physicians tothis infrequently seen malignancy.